2022
DOI: 10.1007/s13201-022-01712-5
|View full text |Cite|
|
Sign up to set email alerts
|

Microplastic pollution in sediments in the urban section of the Qara Su River, Iran

Abstract: Microplastic pollution is an emerging threat to marine environments with potential environmental, social, economic, and health consequences and has become a major global environmental issue. The objective of the present study was to evaluate microplastic contamination in the ecosystem of the Qara Su River in Ardabil, Iran. Fifteen sampling sites along the Qara Su River in the Ardabil urban area were selected to collect sediment samples. The abundance and morphological characteristics of microplastics were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…Published data suggest that predominant particles may include fibers (up to 77%) [95] and fragments (up to 73%) [96]. However, in most studies, fibers are identified as the predominant microplastic particles [97]. The size of microplastic fragments and films in water ranged from 250-100 µm in the largest dimension, while the size of fibers along the length ranged from 100 to 500 µm, consistent with published data [98].…”
Section: Analysis Of Mp Content In Sediment Samplessupporting
confidence: 77%
“…Published data suggest that predominant particles may include fibers (up to 77%) [95] and fragments (up to 73%) [96]. However, in most studies, fibers are identified as the predominant microplastic particles [97]. The size of microplastic fragments and films in water ranged from 250-100 µm in the largest dimension, while the size of fibers along the length ranged from 100 to 500 µm, consistent with published data [98].…”
Section: Analysis Of Mp Content In Sediment Samplessupporting
confidence: 77%
“…From an ecological perspective, sediments are regarded as the primary and most important component of water systems and have been identified as a location for the deposition of a variety of contaminants, including MPs [61]. The worldwide distribution of MPs in the marine environment is well-established based on the information presented thus far.…”
Section: Microplastics In Sedimentsmentioning
confidence: 99%